2019
DOI: 10.3390/nano9101491
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Catalytic Activity and Durability of PtFe Alloy Catalysts for Oxygen Reduction Reaction Through Controlled Carbon Shell Formation

Abstract: Demand on synthetic approaches to high performance electrocatalyst with enhanced durability is increasing for fuel cell applications. In this work, we present a facile synthesis of carbon shell-coated PtFe nanoparticles by using acetylacetonates in metal precursors as carbon sources without an additional polymer coating process for the carbon shell formation. The carbon shell structure is systematically controlled by changing the annealing conditions such as the temperature and gas atmosphere. PtFe catalysts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In this respect, carbon-based graphitic or graphene-like coatings were found to be more promising, as they do not only inhibit oxidation, but also suppress the aggregation of nanoparticles [7,14] while preserving (or even increasing) the catalytic activity of the Fe-Pt systems. [8][9][10][11] Model studies carried out under idealized ultrahigh vacuum (UHV) conditions revealed that epitaxial graphene (Gr) may act as a protective layer against oxidation of metal single-crystal surfaces, including those of catalytically-active [111]-oriented platinum (Pt(111)) [15][16][17] and ferromagnetic nickel (Ni(111)). [18] Even though the Gr layer covers the surface of the metal, it still allows the diffusion of oxygen atoms chemisorbed on the metal substrate to the confined space between the carbon sheet and the metal support [19][20][21] and further reaction of gaseous species (e.g., carbon monoxide (CO)) with the oxygen atoms residing underneath graphene (which is referred to as catalytic reactions "under cover" [22] ).…”
Section: Doi: 101002/admi202002172mentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, carbon-based graphitic or graphene-like coatings were found to be more promising, as they do not only inhibit oxidation, but also suppress the aggregation of nanoparticles [7,14] while preserving (or even increasing) the catalytic activity of the Fe-Pt systems. [8][9][10][11] Model studies carried out under idealized ultrahigh vacuum (UHV) conditions revealed that epitaxial graphene (Gr) may act as a protective layer against oxidation of metal single-crystal surfaces, including those of catalytically-active [111]-oriented platinum (Pt(111)) [15][16][17] and ferromagnetic nickel (Ni(111)). [18] Even though the Gr layer covers the surface of the metal, it still allows the diffusion of oxygen atoms chemisorbed on the metal substrate to the confined space between the carbon sheet and the metal support [19][20][21] and further reaction of gaseous species (e.g., carbon monoxide (CO)) with the oxygen atoms residing underneath graphene (which is referred to as catalytic reactions "under cover" [22] ).…”
Section: Doi: 101002/admi202002172mentioning
confidence: 99%
“…In this respect, carbon‐based graphitic or graphene‐like coatings were found to be more promising, as they do not only inhibit oxidation, but also suppress the aggregation of nanoparticles [ 7,14 ] while preserving (or even increasing) the catalytic activity of the Fe–Pt systems. [ 8–11 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These efforts resulted in promising ORR catalysts which can be broadly classified into three categories: non-PGM metal catalysts [2], metal-free catalysts especially hetero-atom doped carbons [3] and hybrids of non-PGM catalysts with carbon nano-structures [4]. Amongst these three, the third type of carbon-metal hybrids which consists of nano sized non-PGM metal compounds of iron [5], cobalt [6], manganese [7] etc. embedded/dispersed/anchored on nano scaled carbons such as graphene [8], carbon nanotubes [9] and carbon nanofibers [10] have rapidly evolved as attractive alternatives to PGM based ORR electro-catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…However, among the factors hampering the widespread application of PEMFCs, are the high-cost and low-performance electrocatalysts, which are responsible for accelerating the sluggish oxygen reduction reaction (ORR) at the cathode, and still need to be improved [10,11]. Pt/C, the current state-of-the-art ORR catalyst, suffers from inherent scarcity, insufficient stability, and high cost [12,13]. Although nonprecious metal catalysts, such as Fe-, Co-, Cu-, and Ni-based materials, can lower the cost, activity and metal leaching are the two major issues to be solved [14][15][16].…”
Section: Introductionmentioning
confidence: 99%